The ethical legitimacy of autonomous Weapons systems: reconfiguring war accountability in the age of artificial Intelligence - Jie Guo (Ethics & Global Politics)
Recent advancements in artificial intelligence have intensified debates on deploying Autonomous Weapons Systems (AWS) in warfare. Proponents justify AWS on grounds of (1) enhanced military efficiency and reduced soldier casualties, (2) improved compliance with international humanitarian law (IHL) through algorithmic precision, and (3) operational necessity in high-threat environments. This paper critically examines these arguments, contending that they fail to establish the ethical legitimacy of AWS. It argues that AWS fundamentally undermine moral accountability in war, exacerbate risks to civilians, and corrode human agency in lethal decision-making. The analysis concludes that existing ethical and legal frameworks cannot adequately govern AWS, necessitating a reconfiguration of accountability paradigms.